2012
DOI: 10.2319/031911-195.1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of malocclusion on adolescents' dissatisfaction with dental appearance and oral functions

Abstract: Objective: To investigate the impact of malocclusion on adolescents' dissatisfaction with dental appearance and oral functions and to identify components of malocclusion that may contribute to these outcomes. Materials and Methods: The sample comprised 704 secondary school adolescents aged 12 to 13 years from Balneá rio Camboriú , Brazil. A trained and calibrated orthodontist examined the severity of malocclusion using the Dental Aesthetic Index (DAI). A pretested questionnaire was used to assess reported dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 25 publications
9
51
0
2
Order By: Relevance
“…3,4 Furthermore, it can be used and adapted globally and crossculturally without any modification. [5][6][7] Unlike the IOTN, the DAI eliminates the need of a separate instrument to assess the aesthetic component.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Furthermore, it can be used and adapted globally and crossculturally without any modification. [5][6][7] Unlike the IOTN, the DAI eliminates the need of a separate instrument to assess the aesthetic component.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Particular types of malocclusion seems to affect satisfaction with one's dental appearance, facial appearance, general appearance, and perceived attractivness. 2,[7][8][9] The high prevalence rates in different populations demonstrate that malocclusion is a public health problem that requires the planning and implementation of intervention strategies. 10,11 While orthodontic treatment is an effective manner to treat different types of malocclusion 12,13 and can lead to an improvement in quality of life, 4,13,14 the desire to undergo treatment has been explored little in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…At the moment, most of the studies that assessed the impact of malocclusion on OHRQoL of preschoolers used convenience sample of patients who sought dental treatment 6,15 . Therefore, to our knowledge, this is one of the few study that assessed this issue in a representative sample.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, it has been shown that the prevalence of malocclusion can be considered a public health problem, with 22.01% of children under 5 years old presenting slight occlusal problem and 14.45% had moderate or severe problem 4 . However, the exclusively use of such normative indicators has been considered inadequate for measuring oral health and orthodontics treatment needs [5][6] . It has been proposed that any criteria for definition of treatment needs should take into consideration how the health/ disease interferes with children's daily activities and quality of life [7][8] .…”
Section: Introductionmentioning
confidence: 99%